2018
DOI: 10.1007/s10006-018-0720-z
|View full text |Cite
|
Sign up to set email alerts
|

The use of intra-articular analgesics to improve outcomes after temporomandibular joint arthrocentesis: a review

Abstract: There is inconclusive evidence in literature on the benefits of using intra-articular analgesics after TMJ arthrocentesis. Well-designed high-quality RCTs with standard protocol studying the effects of intra-articular opioids and NSAIDS after TMJ arthrocentesis would provide stronger evidence on its use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…The proportion men: women were of 8:1, similar to the ones previously found in the literature [13, 28]. The higher incidence of DDWOR in women may be explained by some female characteristics, such as a higher muscle laxity, higher intra-joint pressure and hormonal changes [1, 29].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The proportion men: women were of 8:1, similar to the ones previously found in the literature [13, 28]. The higher incidence of DDWOR in women may be explained by some female characteristics, such as a higher muscle laxity, higher intra-joint pressure and hormonal changes [1, 29].…”
Section: Discussionsupporting
confidence: 83%
“…The arthrocentesis technique was introduced at about 30 years ago [8] and it has been largely used along with other treatments, such as infiltrations of sodium hyaluronate [12], intra-articular analgesics [13], corticosteroids [14] and platelet rich plasm [15]. However, the literature has showed that an investigation regarding the isolated effects of the arthrocentesis over the DDWOR along with a clinical analysis performed with the aid of the Magnetic Resonance Imaging (MRI) may elucidate some of the benefits of this therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The minimally invasive treatments include the therapies that require intraarticular injections, arthrocentesis, or arthroscopy. They are used to clean or drain the articular cavity, to deliver intraarticularly active substance like drugs (NSAIDs and corticosteroids [35][36][37], biologically-active compounds (for example platelet-rich plasma [38]), or enhance lubrication (hyaluronic acid (Figure 3) [35]). Current clinical therapies using intraarticular injections are effective in pain relief at an early stage of disease but fail to alleviate chronic pain.…”
Section: Treatment Of Tmdmentioning
confidence: 99%
“…Several clinical trials have attempted to improve the efficacy of TMJ arthrocentesis by injecting corticosteroids, sodium hyaluronate, platelet-rich plasma, etc into the joint space. [5][6][7] Experience from arthroscopy procedures on knee joints has demonstrated that intra-articular analgesics may be injected at the end of the procedure to provide early pain relief. 8,9 Inspired by these trials, several clinicians have also experimented with the use of intra-articular analgesics after TMJ arthrocentesis.…”
mentioning
confidence: 99%
“…8,9 Inspired by these trials, several clinicians have also experimented with the use of intra-articular analgesics after TMJ arthrocentesis. 10,11 In 2018, Gopalakrishnan et al 5 conducted a systematic review to analyse the evidence on the efficacy of such intra-articular drugs after TMJ arthrocentesis. After assessing six studies of which just four were randomised controlled trials (RCTs), the authors were unable to demonstrate any conclusive evidence on the use of intra-articular non-steroidal anti-inflammatory drugs (NSAIDs) or opioids after TMJ arthrocentesis.…”
mentioning
confidence: 99%